Biology-inspired engineering for circular bioeconomy systems - Brahm P. Verma; James W. Jones (Journal of Biological Engineering)
Abstract This article presents perspectives on the need to transition from the current unsustainable consumptive fossil-based linear (take-make-use-dispose) systems that produces huge quantities of wastes, pollutes land, water and air, and contributes to climate change to sustainable bio-based circular (take-make-use-decay-reuse) systems. In the article, the word ‘fossil’ refers to all forms of mined carbon and minerals from the Earth, including water from aquafers, which cannot be replenished at the rate that will maintain their capacity to provide for the future. The natural world through its many circular systems uses energy and renewable resources to perform functions that produce zero waste. One organism’s waste becomes another organism’s food, material, and energy, forming a circular loop (take-make-use-decay-reuse). Over the past 4 years, deliberate engagements with leaders of multiple disciplines and stakeholders resulted in conclusions that the problems of the complex biologically active systems (biosystems) that are intertwined with natural systems and socio-economic systems can only be addressed by having a robust culture of convergent science and engineering and systems-thinking for transitioning from linear fossil-based to circular bioeconomy systems. We present the need and propose forming a multidisciplinary professional society alliance to promote and support networks of multidisciplinary teams to address problems of complex, intertwined bio-natural-socio-economic systems of systems. This article proposes that the Institute of Biological Engineering (IBE), a society whose primary objective is to “to apply biology-inspired engineering principles to design systems to improve the quality of the human condition”, and inculcates a culture of convergent science and engineering that has members representing expertise of multiple science and engineering discipline, is potentially an excellent candidate to play a pivotal role in designing innovative solutions for advancing sustainable circular bioeconomy systems.